Gender differences in the antianhedonic effects of repeated ketamine infusions in patients with depression - Zheng, Wei; Yang, Xin-Hu; Gu, Li-Mei; Tan, Jian-Qiang; Zhou, Yan-Ling; Wang, Cheng-Yu; Ning, Yu-Ping (Frontiers in Psychiatry, 2022)
Objectives: Subanaesthetic ketamine (0.5 mg/kg/40 min intravenous infusion) produces rapid and robust antianhedonic effects in subjects with mood disorders, independent of other depressive symptoms. The objective of this study was to examine potential differences in rate of antianhedonic response to ketamine in males and females, which has not been previously examined. Methods: A total of 135 patients with depression (68 males, 67 females) who received six intravenous infusions of ketamine (0.5 mg/kg/40 min) during 2 weeks were enrolled. The anhedonia subscale of the Montgomery–Åsberg Depression Rating Scale (MADRS) was utilized to measure anhedonic symptoms. Antianhedonic remission and response were defined as ≥75% and ≥50% improvement of anhedonic symptoms at 24 hours after the sixth ketamine infusion (day 13). Results: Antianhedonic response (50% versus 47.8%, p>0.05) and remission (26.5% versus 14.9%, p>0.05) rates did not differ significantly between males and females. A linear mixed model revealed a nonsignificant between-group difference in MADRS anhedonia subscale scores (F (1, 132.5)=1.1, p=0.30). Females reported a significantly larger reduction in anhedonic symptoms than males at the 2-week follow-up (p<0.05). Conclusion: The rates of antianhedonic response and remission to multiple ketamine infusions for the treatment of depression were similar between males and females. These findings should be verified by future studies, preferably randomized controlled trials (RCTs).